Transformasi Manajemen Keuangan dan Operasional: Pendampingan untuk Peningkatan Daya Saing Street Coffee Seller di Surabaya - Nugroho, Robertus Adi; Reswari, Puji Ardhana; Rosyadi, Jessica Angelia; Aditama, Eurico Arya (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service aims to enhance managerial and financial capacities of the Street Coffee Seller community in Surabaya through a community service approach. Conducted by the Management Study Program of Universitas Katolik Darma Cendika Surabaya from February to June 2024, the community service method involved preparatory stages including initial observation, SWOT analysis, and development of training materials. The mentoring process encompassed financial management training using the Financial Information Management Application System (SIAPIK) and the establishment of Standard Operating Procedures (SOP) for operational management. Field practice stages allowed for direct application and evaluation of acquired knowledge and skills. Results demonstrated significant improvements in operational efficiency, business sustainability, and community self-reliance enhancement. This approach is envisioned as a model for empowering other SMEs in Indonesia